Designing Emotional Intelligence Measures For Performance In High-Risk Jobs - Mai S., Ishak; Zabidah, Putit; Norehan, Zulkiply; Kartini, Abdul Ghani; Nur Fatihah, Mat Yusoff (Universiti Malaysia Sarawak (UNIMAS), 2015)
Airplane crash, industrial accidents, earthquakes, massive floods, economic crisis; just to name a few of the challenges the 58-year old Malaysia is facing recently. The increase of threats in the form of economic crisis, disasters, terrorism, and crime, has increased health and safety risks in job sectors defined as ‘’high-risk’’ - mining, manufacturing, construction, agricultural, healthcare, emergency responses, security and military. Job environment in these sectors became more complex, tense, and vulnerable to occupational hazards, such as accidents, and stress and fatigue implicated health risks. Occupational Safety and Health Act (1994) is implemented to safe-guard safety and health, where the psychological factors fast became part of the recruitment and selection criterions. The specification of EQ criterions and measures for recruitment and selection, specifically for use of recruitment for high-risk jobs, however, was oftenly done lacking the validity, fairness and ethical standards. Content validity was oftenly justified based on feedbacks from only the superiors in the specific company, since in most cases, EQ consultants were hired top-down by the company superiors. This has huge legal and ethical implications. For EQ to be a legal recruitment criterion, the dimensions and criterions must be both: studied in the best scientific rigor - validated directly to the job incumbent's experience on the job, and, validated to represent across the high-risk occupational groups of similar characteristics. This study will develop and validate a comprehensive Occupational Emotional Intelligence Index based on the competency requirements of executive and non-executive front-liners in 7 high-risk sectors in Kuala Lumpur, Sarawak and Sabah. Focus group, emotional task analysis and critical incident interviews will be used to develop and validate EQ dimensions and criterions required for the job competency. The yielded Model and Index will provide a scientifically validated EQ dimensions and criterions required by the competency standards of the high-risk jobs. This Index will serve as a comprehensive reference for the recruitment and selection of executive and non-executive front-liners across Malaysian high-risk occupational groups. It is hoped that it will help minimise the risk of selection unfairness and bias, hence, legal implications.